2020
DOI: 10.5387/fms.2019-28
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy is involved in the sclerotic phase of systemic sclerosis

Abstract: Autophagy is an essential intracellular selfdegradation system, and is known to maintain the homeostatic balance between the synthesis, degradation, and recycling of cellular proteins and organelles. Recent studies have suggested a possible role of autophagy in systemic sclerosis (SSc) ; however, differences in autophagy among pathological phases of SSc have not yet been examined. Therefore, in the current study we investigated the expression pattern of an autophagosome marker protein, microtubuleassociated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In our study, the microtubule-associated protein 1A/1B light chain 3B (MAP1LC3B), which is a marker of the autophagosome, was overexpressed. This protein was also expressed in the skin of an SSc mouse model and patients ( 34 ). Moreover, ras-related protein 21 (a protein involved in autophagosome–lysosome fusion) was overexpressed under dcSSc ATA+ purified IgG conditions ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the microtubule-associated protein 1A/1B light chain 3B (MAP1LC3B), which is a marker of the autophagosome, was overexpressed. This protein was also expressed in the skin of an SSc mouse model and patients ( 34 ). Moreover, ras-related protein 21 (a protein involved in autophagosome–lysosome fusion) was overexpressed under dcSSc ATA+ purified IgG conditions ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Malfunctional autophagy is believed to play a key role in SSc, as evidenced by the upregulation of autophagy in the fibrotic skin of SSc patients with increased expression levels of LC3, Beclin1, and ATG7, in addition to downregulated protein levels of p62 (108,139). Similarly, activation of autophagy in fibroblasts was also observed in murine models of pulmonary or dermal fibrosis, especially in the sclerotic phase compared to the edematous phase, suggesting an association between abnormal activation of the autophagic degradation system and fibrosis in SSc (139,140). Moreover, inhibition of the PI3K/Akt/mTOR signaling pathway reduced the production of the fibrotic cytokine connective tissue growth factor (CTGF) and collagen I in SSc fibroblasts via downregulation of HIF-1a (141).…”
Section: Systemic Sclerosismentioning
confidence: 98%
“…Studies on skin specimens from SSc patients have shown that impaired autophagy contributes to fibrotic phenotype in this disease [ 71 , 72 , 73 ]. Namely, assessment of key autophagic molecule LC3 by immunofluorescence on skin punch biopsies of SSc patients and control samples showed higher expression of LC3 and increased autophagy in patients compared to healthy controls [ 71 ].…”
Section: Fibroblasts—function and Transformation Into Myofibroblasts ...mentioning
confidence: 99%
“…This finding is in concordance with results of Mori et al, who described the increased number of intracellular LC3-positive puncta in bleomycin-induced mouse scleroderma skin and in the skin of SSc patients in sclerotic phase. This result reflects autophagy activation and its potential effect on disease progression [ 73 ]. Dumit at al.…”
Section: Fibroblasts—function and Transformation Into Myofibroblasts ...mentioning
confidence: 99%